National income of India : growth and distribution 1950-51 to 1960-61 - Indian Merchants' Chamber (Bombay : IMC Economic Research and Training Foundation, 1963)
The object of this study is to usefully explore the sphere of research activity on national income in its practical aspect.
Includes index.
Includes bibliographical references: p. 267-268.
osa 04/12/2018
Loans
Keywords: Income; India